2019
DOI: 10.1002/2050-7038.12115
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimal energy and reactive power management in smart distribution networks: An info‐gap multi‐objective approach

Abstract: Summary Distributed energy resources (DERs) are main components for smart distribution networks (SDNs). Generally, energy and reactive power dispatch scheduling problems are managed separately in SDNs. In this paper, a robust simultaneous active/reactive scheduling framework is presented for SDNs. In order to handle the uncertainties of wind power generation, upstream grid prices, and load demand forecasting in a robust framework, information gap decision theory (IGDT) technique is proposed. The proposed robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The accessible reactive power at any instant from an SI depends on the active power output of a SI. Hence, it is essential to forecast PV power 8 . Fluctuating PV power is more efficiently estimated if the PV power is predicted accurately.…”
Section: Modeling Of Probabilistic Pv Power Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessible reactive power at any instant from an SI depends on the active power output of a SI. Hence, it is essential to forecast PV power 8 . Fluctuating PV power is more efficiently estimated if the PV power is predicted accurately.…”
Section: Modeling Of Probabilistic Pv Power Forecastingmentioning
confidence: 99%
“…In order to mitigate the voltage fluctuation problem due to massive penetration of DER in the network, 2,3 new‐generation smart inverters (SI) are incorporated by DERs to fulfill the ancillary service requirement, at reduced cost without any additional resources 4‐6 . In recent years, it is also observed that demand response (DR) programs are not only acting as a tool to allow customers to participate in the electricity market to improve the economic efficiency and reliability of distribution network 7‐9 but also improve the network voltage. In peak hours kW reduction by consumers have a high effect on change in network voltage due to high R/X ratio of the distribution network 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Boost converter is a step‐up chopper that provides larger output voltage compared to its input voltage. From prior work, 6‐28 it is observed that several types of linear, nonlinear, optimized, and advanced control approaches are already applied in Boost converters.…”
Section: Boost Convertermentioning
confidence: 99%
“…Modeling and advanced control architectures of switching converters which having nonminimum phase problem have been reported by Banerjee et al, Ling et al, Rana et al [20][21][22][23] Robust voltage control with wide parametric variations of switching converters for renewable energy applications are reported in prior works. 24,25 The comparison between different classical and advanced control methods like IMC, SMC for a Boost converter are discussed in Ghosh and Banerjee. 1 Advanced robustness studies, adaptive sliding mode based control and nonlinear dynamics analysis by varying different control parameters in switching converters are reported in recent literatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation